2009
DOI: 10.1007/s00213-008-1453-8
|View full text |Cite
|
Sign up to set email alerts
|

MDMA: On the translation from rodent to human dosing

Abstract: The recent paper in this journal by Goni-Allo et al. (2008) was a welcome addition to the literature on the effects of MDMA in rodents because it examined functional changes and related them to the systemic exposure (e.g., plasma concentrations) of the drug. Such pharmacodynamicpharmacokinetic (or quantitative pharmacology) studies are vital if we are to attempt to relate preclinical findings to the possible acute and long-term consequences of human ingestion of MDMA. The debate on whether preclinical findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
65
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 27 publications
4
65
1
Order By: Relevance
“…Due to rapid MDMA clearance in rats, repeated s.c. injections of low-dose MDMA in this species might be an acceptable model for po doses administered to humans, but this hypothesis needs to be tested. In any case, the present findings do not support the notion that rats must receive 4-fold-higher doses of MDMA to achieve peak plasma concentrations similar to those observed in humans (Green et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Due to rapid MDMA clearance in rats, repeated s.c. injections of low-dose MDMA in this species might be an acceptable model for po doses administered to humans, but this hypothesis needs to be tested. In any case, the present findings do not support the notion that rats must receive 4-fold-higher doses of MDMA to achieve peak plasma concentrations similar to those observed in humans (Green et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…In two rat studies employing doses of ,10 mg/kg, evidence for MDMA nonlinear accumulation was reported (Chu et al, 1996;), similar to the human situation (Mas et al, 1999;de la Torre et al, 2000;Kolbrich et al, 2008b). By contrast, Green et al (2009) and Hirt et al (2010) suggested linear MDMA kinetics in rat.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The only information is from an abuser that self-reported use of 4-MA by oral (160 mg) and intramuscular (80-120 mg) route (EMCDDA, 2012). The human equivalent doses of the range used (2.5 -10 mg/Kg) in the present study, although given subcutaneously, are 30 -120 mg [16], which are in agreement with those reported as psychostimulants.…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps the optimal strategy for relating MDMA data from animals to humans is to compare pharmacokinetic parameters across species (de la Green et al, 2009). Clinical investigations have examined plasma concentrations of MDMA and its metabolites after the administration of psychoactive doses (Mas et al, 1999;de la Torre et al, 2000;Kolbrich et al, 2008b), and comparable low-dose experiments have been performed in monkeys (Banks et al, 2007;Mueller et al, 2008).…”
mentioning
confidence: 99%